2015
DOI: 10.1111/ggi.12600
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of posture as a measure of physical function in elderly individuals: Use of a digitalized inclinometer to assess trunk inclination

Abstract: Our results show that the sternum inclination as a measure of physical function in elderly men and women has construct validity. We determined reference values for sternum inclination of which trend by age was considered. Geriatr Gerontol Int 2016; 16: 1068-1073.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The following methods and tools were used to assess body posture: SpinalMouse [8, 21 -24], occiput-to-wall distance (OWD) [25 -27], method using 1.7 cm blocks [28], flexicurve ruler [29,30], Cobb angle [24,26,27], photogrammetry/Moiré method [31], method with photographic recording [32] and digital inclinometer [33]. Foot posture was assessed using the Foot Posture Index (FPI) [34,35], which tests foot characteristics across six domains: foot posture, foot deformity and lesions, plantar tactile sensation, toe muscle strength and foot pain, and a three-dimensional foot scanner (Footstep PRO, Dream GP Company, Japan) [36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following methods and tools were used to assess body posture: SpinalMouse [8, 21 -24], occiput-to-wall distance (OWD) [25 -27], method using 1.7 cm blocks [28], flexicurve ruler [29,30], Cobb angle [24,26,27], photogrammetry/Moiré method [31], method with photographic recording [32] and digital inclinometer [33]. Foot posture was assessed using the Foot Posture Index (FPI) [34,35], which tests foot characteristics across six domains: foot posture, foot deformity and lesions, plantar tactile sensation, toe muscle strength and foot pain, and a three-dimensional foot scanner (Footstep PRO, Dream GP Company, Japan) [36].…”
Section: Resultsmentioning
confidence: 99%
“…Body balance was assessed using more accurate methods of measurement, such as stabilometry, force plate [14,21,22,24,29,36], and functional tests such as the Timed Up and Go (TUG) test [8, 23, 32 -35], functional reach (FR) [8], Berg Balance Scale (BBS) [30], one-led stance [23,32,33], Four-Square Step Test (FSST) [34,35] and feet-together stance, semitandem and tandem standing [25]. Table 2 -Characteristics of the studies with regard to methodologies, sample profile, outcomes and tools used for assessing body posture, balance and falls risk Table 2 -Characteristics of the studies with regard to methodologies, sample profile, outcomes and tools used for assessing body posture, balance and falls risk -Characteristics of the studies with regard to methodologies, sample profile, outcomes and tools used for assessing the feet and the ankle, as well as balance and falls risk The methodological quality of the studies is shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main feature of the intelligent sensor system is to provide more reliable and complete important data information to the network through the communication interface. Compared with traditional sensors, smart sensors have intelligent performance such as self-calibration, self-evaluation of working status, self-repair of faults, compensation and measurement [18][19]. The intelligent sensor system can optimize the operation of each intelligent sensor in the system and perform data processing, and has a further understanding and improvement of the data measurement and measurement environment.…”
Section: Smart Sensor Systemmentioning
confidence: 99%